Philosophy of Developmental Biology - Weber, Marcel (Humanities, 2022)
Taking a causal perspective, this Element examines to what extent and how developmental biology, having turned molecular about four decades ago, has been able to meet the vitalist challenge. This title is also available as Open Access on Cambridge Core.